Estimasi Angkutan Sedimen Total pada Sungai Indulung Kota Tarakan - Asta Asta; Fransisca Noni Sepliana (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
As the population increases, the water demand is also increasing. The river flow is the dominant water source to fulfill the needs of human life, so the river should always be kept sustainable, the way to keep is by trying the cross-sectional capacity of the river stable from sediment deposits. Indulung River is one of the rivers in Tarakan City which is experiencing siltation due to sedimentation. Total sediment analysis was conducted to obtain the value of sediment transport and to obtain a method that can be used as a benchmark in determining the total sediment discharge in the Indulung River, using the Yang method and Bagnold method. From the research results, the average sediment discharge using the Yang method is 4.34 tons/year and Bagnold's method is 2.01 tons/year. Based on the recapitulation, which produces the largest value is the Yang method, with a value of 4.34 tons/year, the Yang method is used as a benchmark for other sediment transport methods.